Design of a compact microstrip antenna at 2.4GHZ - Abdul Ghafar, Nurulrodziah (2005)
With the recent advances in telecommunications, the need for compact antennas has greatly increased. Electronic equipment has rapidly reduced in physical size due to the development of integrated circuits, especially in mobile communications; the demand for the smaller antennas is quite strong. However, requirements on antenna performance on such small equipment are becoming increasingly severe, since the antenna performance should not be significantly degraded as the size become smaller. The microstrip antenna is one of the most preferable for small equipment, especially when a built-in antenna is required. It has many advantages such as low profile and easy fabrication. However for low-frequency applications, the microstrip size becomes too large for practical implementation. One of the problems in microstrip antenna technology is the reduction of the antenna sizes. The aim of this project was to design, fabricate and test a compact microstrip patch antennas operating at 2.4GHz. Three microstrip antennas operating at 2.4GHz was designed, fabricated and tested; a conventional rectangular microstrip antenna, a compact rectangular microstrip antenna with shorted wall method and a compact rectangular microstrip antenna with shorted pin method. Those designs were simulated with Microwave Office software and tested with the Marconi Scalar Analyzer. Both, simulated and measured data were compared and contrasted